Temporal and spatial interactions in sympatric ungulates: Insights from Japanese serow and sika deer - Tomoki Mori; Kensuke Miura; Hiroyuki Takeuchi; Yasuaki Niizuma (PLoS ONE, 2025)
Sympatric species, commonly evolve behavioural mechanisms allowing them to coexist, thereby reducing direct competition for resources. In Japan, since the 1970s, the endemic Japanese serow (Capricornis crispus) and the sika deer (Cervus nippon) have been primarily allopatric. However, due to the rapid expansion of the sika deer population on Japan’s main island of Honshu, the habitats of these two species now overlap. The significant and increasing overlap raises concerns about the potential impacts between these two (now sympatric) ungulates, including changes in distribution, shifts in activity patterns, or displacement due to interspecific competition. In this study, we investigated temporal and spatial segregation between Japanese serow and sika deer, from 2015 to 2017, in Shirakawa Village, Gifu Prefecture, Japan, by means of camera traps. Although our study was limited by a small sample size, it revealed no clear temporal or spatial segregation between the species, suggesting that there is potential for coexistence in shared habitats without pronounced competitive conflict, perhaps due to an abundance of food relative to sika deer density. Nevertheless, during autumn, reduced activity overlap rates, when the relative abundance index (RAI) of sika deer increased, may indicate that Japanese serow have modified their behavior to minimize resource competition. Specifically, during summer, when the RAI of sika deer was low, Japanese serow exhibited cathemeral behavior, whereas in autumn Japanese serow became nocturnal as sika deer RAI values increased. This seasonal adjustment indicates a context-dependent behavioural response that may serve to reduce temporal overlap and mitigate competition. Given the increasing sika deer population, understanding this potential for intensified competition becomes crucial for effective wildlife management and conservation efforts, particularly in maintaining the ecological balance between these species and ensuring the long-term sustainability of their habitats.